Sol-Gel Template Synthesis and Characterization of Lu(2)O(3):Eu(3+) Nanowire Arrays - Hu, Yahua (Micromachines (Basel), 2018)
Uniform Lu(2)O(3):Eu(3+) nanowire arrays were successfully prepared by the sol-gel process using anodic aluminum oxide (AAO) templates. The as-synthesized nanowires are homogeneous, highly ordered, and dense and have a uniform diameter of ~300 nm defined by the AAO templates. The X-ray diffraction and selected area electron diffraction results show that the Lu(2)O(3):Eu(3+) nanowires have a polycrystalline cubic structure, and the crystallite size of the Lu(2)O(3):Eu(3+) nanowires is confined by the AAO template. The nanowires within the AAO template showed good photoluminescence and X-ray-excited optical luminescence performances for Lu(2)O(3):Eu(3+). The emission peaks were attributed to the (5)D(0) → (7)F(J) transitions of Eu(3+) (J = 0, 1, 2, 3).